A computer program for geostatistical and spatial analysis of crop model outputs - Thornton, Philip K.; Booltink, H.W.G.; Stoorvogel, J.J. (Wiley, 1997)
Well-tested computer simulation models of the growth, development, and yield of annual crops are being used for a wide range of purposes, including the prediction of impacts of different management practices and land use systems on food production, farmers' profitability, and the environment. Presentation and interpretation of simulation results can be significantly enhanced through the linking of models with software that allows spatial visualization. Many users of crop simulation models, however, are located in institutions in developing countries where resources are particularly limited. Computer software to perform a variety of spatial analyses was written, which can be run on modest hardware without the need for costly third-party software. The software is an integral part of the Decision Support System for Agrotechnology Transfer (DSSAT), a comprehensive crop simulation model and data system, but can also be run in a stand-alone mode. Users can run spatial simulation experiments and then analyze the results using (i) a geostatistical module to interpolate maps and produce probability surfaces from a network of data points and (ii) a utility that calculates agronomic and economic output statistics from model simulations and maps the results as polygons. The suite of modules, which runs on an IBM-compatible personal computer, interfaces with some widely used third-party GIS software, and the mapping facility enables users to export and import images to a number of common file formats. Research at ILRI has shown the value of incorporating forages and fodder species into sustainable farming systems, but the lack of available seed of adapted forage materials remains a major constraint to their adoption by smallholder farmers. Technical knowledge, access to seed, and economic incentives are essential. Recognizing the need to promote access to forage seed, ILRI (formerly ILCA) established a Herbage Seed Unit in 1989 to address the problem in Sub-Saharan Africa and enhance the incorporation of forages in feed resource development. It was envisaged that this would be achieved by strengthening national capacities to produce forage seed, and training scientists and technicians. This activity has now been expanded to provide a source of tropical forage seed for the establishment of national forage seed production in many countries. Past and current activities in forage seed production at ILRI are presented, and future plans for serving ILRI's global mandate are discussed.